PENINGKATAN BERAT BADAN AKSEPTOR KONTRASEPSI SUNTIK PROGESTIN - Annisa, Farida Ulfah; Wiyati, Nining; Rahmawati, Anita (Poltekkes Kemenkes Yogyakarta, 2013)
Injection contraception is a contraception that chosen by the most acceptors in Indonesia including in Yogyakarta. Its amount reaches 20,549 acceptors or 36.54% with the most acceptors found in Gunungkidul Regency. There are 5,031 acceptors (41.15%). Increasing of the body weight is the highest frequency of the effect of using injection contraception. To determine the description of the increasing of body weight in progestin injection contraception in Paliyan District of Gunungkidul Regency on 2011-2012. Kind of the research that used is descriptive with cross sectional approach, done in Paliyan District on March 25th -April 31st 2013. The subject of the research is all new acceptors of progestin acceptors of progestin injection contraception with completely medical document in Paliyan in January0 December 2011 that amount to 216 acceptors. After obtaining data then it is carried out analysis using mena table. On the whole of 216 acceptor of progestin injection Family Planning Program in Paliyan District, there are 162 acceptors (75%) that experience in increasing of the body weight in the use of 13 months usage. The rate of increasing of the body weight in the second injections is 0.69 kg, the third injection is 1,23 kg, the fourth injection is 1,57 kg, and the fifth injection is 2.02 kg. the body weight o progestin injection contraception acceptor is inclined to increase in its following of repeating injection. The rate of increasing of the body weight for 13 months usage is 2.02 kg